Long after we are gone : a novel - Harris, Terah Shelton (Sourcebooks Landmark, 2024)
""Don't let the white man take the house." These are the last words King Solomon says to his son before he dies. Now all four Solomon siblings must return to North Carolina to save the Kingdom, their ancestral home and 200 acres of land, from a development company, who has their sights set on turning the valuable waterfront property into a luxury resort. While fighting to save the Kingdom, the siblings must also save themselves from the secrets they've been holding onto. Junior, the oldest son and married to his wife for eleven years, is secretly in love with another man. Second son Mance can't control his temper, which has landed him in prison more than once. CeCe, the oldest daughter and a lawyer in New York City, has embezzled thousands of dollars from her firm's clients. Youngest daughter Tokey wonders why she doesn't seem to fit into this family, which has left an aching hole in her heart that she tries to fill in harmful ways. As the Solomons come together to fight for the Kingdom, each of their façades begins to crumble and collide in unexpected ways. Told in alternating viewpoints, Long After We Are Gone is a searing portrait on the power of family and letting go of things that no longer serve you, exploring the burden of familial expectations, the detriment of miscommunication, and the lessons and legacies we pass on to our children."--